The neural underpinnings of repeated skill transfer in human cultural evolution - Øhrn, Heidi; Sjursen, Emilie Pettersen; Specht, Karsten; Hugdahl, Kenneth; Straffon, Larissa Mendoza; Bender, Andrea (Frontiers in Psychology, 2025)
Cumulative cultural evolution (CCE) is a fundamental aspect of human cognition, enabling the refinement and transmission of complex skills across generations. This study explores the cognitive abilities supporting CCE through a transmission chain design using a knot-tying task combined with brain imaging to examine how skills are acquired over successive learning and transmission stages. We obtained data from two chains of multiple generations of participants. Our results revealed generational modifications in knot-tying techniques accompanied by increased prefrontal cortex activation in later generations of learners, possibly suggesting that loss of information due to imperfect copying fidelity increases cognitive demands for working memory. Our study further shows the potential of brain imaging as a viable technique for investigating CCE. By applying functional MRI to track neural activity during the acquisition of knot-tying skills, we provide a novel approach for understanding the cognitive mechanisms that underlie cultural knowledge transfer. Further research integrating neuroimaging with behavioral studies could help clarify how cognitive and neural processes contribute to the accumulation and refinement of cultural knowledge over time.